RSVP a temporal method for graphical authentication. Issue 4 (2nd October 2017) - Cain, Ashley A; Still, Jeremiah D
ABSTRACT: We present a Rapid, Serial, Visual Presentation method (RSVP) for recognition-based graphical authentication. It presents a stream of rapid, degraded images, which makes the object recognition process difficult for casual attackers. Three studies investigated success rates for authenticating, RSVP's resistance to over-the-shoulder attacks (OSAs), approaches for facilitating learnability, and effects of resetting a passcode. We found that participants could successfully authenticate and could not complete OSAs. Learnability was promoted by the presentation of degraded versions of the images during the memorization phase. When a passcode was reset, participants successfully retrained themselves even when the previous passcode was recycled as distractors.